Qualidade ambiental de salas de aula baseada na avaliação do conforto térmico e da qualidade do ar interior - Reis, Danillo Viana Andrade (2023)
Improving indoor environmental quality conditions of buildings is a growing challenge in engineering. The fact that we live around 90% of our lives within this type of environment demonstrates how significant these conditions are for our health and well-being. In this regard, thermal comfort and air quality are key aspects, especially for more vulnerable populations, such as the elderly and children. School environments are places of concern in this context, due the proportion of children among the users, as well as the high density of people and length of stay. This point was widely discussed while reopening schools during the COVID-19 pandemic. The present work aims to evaluate the thermal conditions and air quality of school environments in an integrated approach, which allows obtaining a representative index of the environmental quality of these spaces. So, environmental variables were monitored in 16 classrooms in the city of Aracaju/SE, in order to obtain data comparable to the reference values in the scientific literature. The results were applied equations from literature review, resulting in a normalized representative index of indoor air quality and thermal comfort from each classroom. These indexes were weighted in terms of the importance of each of these criteria, finally obtaining an index referring to the Indoor Environmental Quality of each classroom. An analysis of the ventilation of spaces was also carried out, with ways to observe the possibility of applying a protocol for the use of environments suitable for exceptional situations, of concern with the risk of transmission of respiratory infections. The results indicated a large discrepancy between the thermal conditions and air quality between the climate-controlled environments with air conditioners and the non-conditioned ones. While air-conditioned environments indicated inadequate ventilation conditions in most of the monitoring, those with natural ventilation remained adequate all the time. On the other hand, all rooms without air conditioners presented inadequate thermal conditions, with temperatures above the recommended level, while the other environments showed better conditions. Thus, there is a balance of factors in the global index, but with a predominance of quality for some air-conditioned environments, due to the considerable poor thermal conditions of the rooms of the other typology. The size, positioning and other factors related to the windows were factors of great importance, both in terms of thermal gain and ventilation. It was also possible to observe which rooms could operate properly under a protocol aimed at air renewal. Once again, windows were decisive in the results, with the fans helping in this process. Thus, we can conclude that it was possible to apply a methodology to evaluate the overall quality of these school environments and that this brings good indications for decision-making by managers. These results can guide the application of resources, more assertive biosafety protocols and the discussion of public policies aimed at improving indoor school environments.